Synthetic Polymers as Adsorbents for the Removal of Cd(II) from Aqueous Solutions - Arvand, M.; Shemshadi, R.; Efendiev, A.A.; Zeynalov, N.A. (Asian Journal of Chemistry, 2011)
In the present investigation seven synthetic polymers are used as adsorbents for the removal of Cd(II) from aqueous solution. The equilibrium studies are systematically carried out in a batch process, covering various process parameters that include agitation time, adsorbent dosage and pH of the aqueous solution. It was observed in adsorption and desorption tests that the synthetic polymers showed significant pH dependence, which affect the removal efficiency, robustly. Adsorption behaviour is found to follow Freundlich and Langmuir isotherms. A regeneration study was also carried out.